Tackling Small and Medium Enterprise Problem Loans in Europe - Bergthaler, Wolfgang (Staff Discussion Notes; Staff Discussion Notes ;, 2015)
The global financial crisis has left a large private sector debt overhang and high levels of non- performing loans (NPLs) in several European countries. Small and medium-size enterprises (SMEs) represent a significant and weak segment of the nonfinancial corporate sector. SMEs face a number of legal, financial, and regulatory challenges to restructuring that differ from those of larger corporates, such as a rigid and costly insolvency regime, a higher fixed cost to loan restructuring, and the lack of alternative sources of financing. Given SMEs' large presence and close links to the banking system, addressing the SME loan problem in Europe will be critical for strengthening bank and corporate balance sheets and supporting a more robust and sustained recovery.